Activation of the Wnt/β‐catenin pathway represses the transcription of the β‐amyloid precursor protein cleaving enzyme (BACE1) via binding of T‐cell factor‐4 to BACE1 promoter. Issue 2 (10th November 2014) - Parr, Callum; Mirzaei, Nazanin; Christian, Mark; Sastre, Magdalena
ABSTRACT: Alterations in the Wnt signaling pathway have been implicated in Alzheimer's disease; however, its role in the processing of the amyloid precursor protein remains unknown. In this study, activation of the Wnt pathway by overexpression of the agonist Wnt3a or β‐catenin or by inhibition of glycogen kinase synthase‐3 in N2a cells resulted in a reduction in Aβ levels and in the activity and expression of BACE1 (β‐APP cleaving enzyme). Conversely, inhibition of the pathway by transfection of the antagonists secreted frizzled receptor protein‐1 or dickkopf‐1 produced the opposite effects. Chromatin immunoprecipitation analysis demonstrated that β‐catenin binds specifically to regions within the promoter of BACE1 containing putative T‐cell factor/lymphoid enhancer binding factor‐1 (TCF/LEF) motifs, consistent with canonical Wnt target regulation. Furthermore, cells transfected with β‐catenin mutants incapable of binding to TCF/LEF increased BACE1 gene promoter activity. Interestingly, TCF4 knockdown reversed the effects of Wnt3a activation on BACE1 transcription. We found that TCF4 binds to the same region on BACE1 promoter following Wnt3a stimulation, indicating that TCF4 functions as a transcriptional repressor of BACE1 gene. In conclusion, Wnt/β‐catenin stimulation may repress BACE1 transcription via binding of TCF4 to BACE1 gene, and therefore, activation of the Wnt pathway may hold the key to new treatments of Alzheimer disease.—Parr, C., Mirzaei, N., Christian, M., and Sastre, M. Activation of the Wnt/β‐catenin pathway represses the transcription of the β‐amyloid precursor protein cleaving enzyme (BACE1) via binding of T‐cell factor‐4 to BACE1 promoter. FASEB J . 29, 623‐635 (2015). www.fasebj.org